Development and Validation of a Fanoroho-Based Group Guidance Model for Students' Speaking Politeness - Musdin Musakkir; Sahril Buchori; Abdullah Pandang (Jurnal IPTEK Bagi Masyarakat, 2026)
This study aimed to describe the need for, develop, and examine the validity and practicality of a Yali cultural values-based group guidance model to support students’ speaking politeness at SMP Negeri Hubakma. The study used a Research and Development approach by adapting selected stages of the Borg and Gall model: research and information gathering, planning, preliminary product development, expert validation, revision, limited field testing, and practicality testing. Data were collected through interviews, questionnaires, observations, document analysis, and focus group discussions, then analyzed qualitatively and quantitatively. The findings showed that counselors and students needed a culturally relevant group guidance model to improve speaking politeness. The developed model consists of five stages: Nori Maniek, Kema Laruk Laep, Fanoroho, Halefulen, and Wereg. Material expert validation reached 81.09% and media expert validation 84.45%, both categorized as highly valid. Practicality testing produced scores of 91% from school counselors, categorized as highly practical, and 76% from students, categorized as practical. Therefore, the model is valid, practical, and feasible as an alternative group guidance service to support students’ speaking politeness.